The Framing of the Iraq War on the Cover of the New York Post : An Examination of Headlines Through Framing Theory - Rytö, Mikko (My University, 2026)
This thesis examines The New York Post’s covers in the lead-up and during the Iraq war. The covers are investigated through the lens of framing theory, leaning on prior research on the subject. Episodic framing, which focuses on the salience of individual people and cases, and thematic framing, which focuses on that of underlying societal causes, are looked at separately. The Post is found to have featured the war less as it went on. Its covers and headlines routinely use sensational, emotional, and unabashedly biased language. The Post has a clear preference for the use of episodic over thematic framing. This is unsurprising due to the effectiveness of episodic framing, in conjunction with the aforementioned style of language, is more potent than thematic framing in creating attention grabbing and sensational headlines.
Keywords: Framing Theory, Frames, Iraq War, New York Post, Headlines, Media